Efectos de la educación en los ingresos laborales de la población económicamente activa ocupada en las provincias del departamento de Loreto 2017-2023 - Calero Quinde, Nayelli Jackeline (2025)
The role of education on the levels of labor income of the PEAO was analyzed, considering that the improvement of human capital has a fundamental role in employability and the ability to earn income. For the same, the annual records of public spending on education per inhabitant, the average number of years of schooling and the average income from the work of the PEAO in the provinces of Alto Amazonas, Loreto, Mariscal Ramón Castilla, Maynas, Requena and Ucayali of the department of Loreto during the period 2017 2023. After choosing to exclude the data from 2020 due to its atypicality due to the covid-19 pandemic, a multiple linear regression model was applied and it was determined that when public spending on education per inhabitant of a certain province increases by S/ 100, the labor income of the PEAO in the same province increases by S/ 21.37. Likewise, when the average number of years of schooling increases by 1 additional year, the labor income of the PEAO in the same province increases by S/ 197.45.